Cilostazol Inhibits Accumulation of Triglyceride in Aorta and Platelet Aggregation in Cholesterol-Fed Rabbits - Ito, Hideki; Uehara, Kenji; Matsumoto, Yutaka; Hashimoto, Ayako; Nagano, Chifumi; Niimi, Manabu; Miyakoda, Goro; Nagano, Keisuke (PLOS ONE, 2012)
Cilostazol is clinically used for the treatment of ischemic symptoms in patients with chronic peripheral arterial obstruction and for the secondary prevention of brain infarction. Recently, it has been reported that cilostazol has preventive effects on atherogenesis and decreased serum triglyceride in rodent models. There are, however, few reports on the evaluation of cilostazol using atherosclerotic rabbits, which have similar lipid metabolism to humans, and are used for investigating the lipid content in aorta and platelet aggregation under conditions of hyperlipidemia. Therefore, we evaluated the effect of cilostazol on the atherosclerosis and platelet aggregation in rabbits fed a normal diet or a cholesterol-containing diet supplemented with or without cilostazol. We evaluated the effects of cilostazol on the atherogenesis by measuring serum and aortic lipid content, and the lesion area after a 10-week treatment and the effect on platelet aggregation after 1- and 10-week treatment. From the lipid analyses, cilostazol significantly reduced the total cholesterol, triglyceride and phospholipids in serum, and moreover, the triglyceride content in the atherosclerotic aorta. Cilostazol significantly reduced the intimal atherosclerotic area. Platelet aggregation was enhanced in cholesterol-fed rabbits. Cilostazol significantly inhibited the platelet aggregation in rabbits fed both a normal diet and a high cholesterol diet. Cilostazol showed anti-atherosclerotic and anti-platelet effects in cholesterol-fed rabbits possibly due to the improvement of lipid metabolism and the attenuation of platelet activation. The results suggest that cilostazol is useful for prevention and treatment of atherothrombotic diseases with the lipid abnormalities.